2015
DOI: 10.4274/tjh.2014.0204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alpha-Thalassemia Mutations in Cases with Hypochromic Microcytic Anemia: The İstanbul Perspective

Abstract: Objective:Alpha thalassemia syndromes are caused by mutations on one or more of the four α-globin genes. Mutations could be either more commonly deletional or non-deletional. As some deletions (3.7 and 4.2) cause α+-thalassemia, some cause (-20.5, MED, THAI, FIL) α0 -thalassemia. The aim of this study was to determine alpha thalassemia mutations in patients with unsolved hypochromic microcytic anemia and to evaluate types of mutations.Material and Methods:Two hundred six patients with hypochromic microcytic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
7
2
5
Order By: Relevance
“…In a study performed by Çelik et al in the southern region of Turkey, -α 3.7 deletion frequency was reported as 43.2% (10). Karakaş et al reported the frequency of -α 3.7 deletion as 39% in a study they performed on patients with hypochromic mi-crocytic anemia living in Istanbul (11). Our data are in accordance with the results of this study carried out in Istanbul, which is located close to the Trakya region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study performed by Çelik et al in the southern region of Turkey, -α 3.7 deletion frequency was reported as 43.2% (10). Karakaş et al reported the frequency of -α 3.7 deletion as 39% in a study they performed on patients with hypochromic mi-crocytic anemia living in Istanbul (11). Our data are in accordance with the results of this study carried out in Istanbul, which is located close to the Trakya region.…”
Section: Discussionsupporting
confidence: 92%
“…-α 4.2 , another type of deletion underlying α + thalassemias, is reported less frequently than the −α 3.7 deletion. Karakaş et al reported the frequency of -α 4.2 deletion as 4.2%, and Onay et al reported that they did not detect any -α 4.2 deletion (6,11). In our study, the -α 4.2 deletion was found in only one case as compound heterozygous with the −α 3.7 deletion.…”
Section: Discussioncontrasting
confidence: 43%
“…We detected 198 patients with HbH disease when we searched articles from PubMed related to Turkish patients with HbH disease [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. When the results of our study were added to that number, we found 471 HbH cases to date from Turkey, and this number is fairly high ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of Hb Adana varies by country and ethnicity in the thalassemia belt but these reports likely underestimate the true incidence as many patients in these areas do not have access to accurate genetic diagnosis. A low incidence was found in countries such as Turkey (0.5–0.6%), Iran/Iraq (1–2.5%), and China (1%) . Countries found to have a higher prevalence included Saudi Arabia (11.6%) and Indonesia (16%) .…”
Section: Discussionmentioning
confidence: 99%